Nutritional effects of commercialization of a woman's crop: Irrigated rice in The Gambia - von Braun, Joachim; Johm, Ken B.; Puetz, Detlev (International Food Policy Research Institute, 1994)
The Gambia (West Africa) had a population of approximately 0.75 million and a total agricultural cultivated area of only 1,850 square kilometers in 1987-88. By virtue of its small size, The Gambia is prone to an open market economy, and commercialization and specialization of agriculture have to be elements of any viable growth strategy. Besides its small size, The Gambia is almost completely surrounded by Senegal, except for the Atlantic Ocean on the west. Consequently, there is vigorous cross-border trade in agricultural commodities and inputs, in addition to basic nonfood commodities. In 1985, reexport of goods accounted for 69 percent of total domestic exports.